Current Management of Hepatic Encephalopathy. (November 2018) - Acharya, Chathur; Bajaj, Jasmohan
Abstract Hepatic encephalopathy is a state of brain dysfunction resulting from decompensation of cirrhosis. The mortality and morbidity associated with the overt form of hepatic encephalopathy are high, and even the covert form associates with poor outcomes and poor quality of life. We know that the dysfunction is not just an acute insult to the brain but rather results in long-standing cognitive issues that get worse with each episode of HE. Hence, there is an urgency to accurately diagnose these conditions, start appropriate therapy, and to maintain remission. Currently, we have two mainstay pharmacological treatment options (lactulose and rifaximin), but the narrative is evolving with new therapies under trial. Microbiome manipulation resulting in a favorable change to the gut microbiota seems to be a promising new area of therapy.